Mutations in CHMP4C cause dilated cardiomyopathy via dysregulation of autophagy. (25th November 2020) - Zhou, N.W; Tang, L; Jiang, Y.Y; Li, X.J; Zhao, W.P; Pan, C.Z; Wang, X.L; Shu, X; Qiu, Z.L; Ge, J.B
Abstract: Background: Gene mutations have been implicated in DCM. However, due to the difficulty of clinical genetic diagnosis, more causal genes potentially related to DCM remain to be discovered. Methods: We screened for gene mutations in more than 400 cases from families with hereditary cardiovascular disease using whole-exome sequencing. Then we validated biological functions of CHMP4C mutations in zebrafish models. To further assess the mechanism of CHMP4C mutations, we evaluated the potential signaling pathway in the cells. Results: We identification of CHMP4C variants that segregated with DCM variants in four families from a total of 411 families via whole-exome sequencing. We further validate the function of CHMP4C in heart function in zebrafish models and found that over-expression of CHMP4C variants in zebrafish resulted in cardiac malformation, pericardial edema and increased heart rate, consistent with CHMP4C mutation-associated findings in DCM patients. Furthermore, we found that mutations in CHMP4C impaired autophagy and activated apoptosis in HEK293T cells, suggesting that the molecular mechanism of CHMP4C is involved in heart development. Conclusions: CHMP4C is a novel candidate gene for DCM and may play a critical role in cardiac development by regulating autophagy. Funding Acknowledgement: Type of funding source: None